2012
DOI: 10.1016/j.theriogenology.2012.06.018
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo quality of bovine embryos in vitro produced with sex-sorted sperm

Abstract: In this work we analyzed the effects of three culture systems on developmental ability of bovine embryos in vitro produced with sexed sperm, the survival to vitrification (cryologic vitrification method) of such blastocysts, and their pregnancy rates after embryo transfer to recipients, both as fresh and after vitrification/warming. Finally, we measured the accuracy of the sorting protocol by a polymerase chain reaction-based method to validate the embryo sex at blastocyst stages. We confirmed an individual ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 64 publications
(68 reference statements)
1
32
0
8
Order By: Relevance
“…We observed that bovine IVP embryos survived vitrification at higher rates than freezing by the slow-controlled rate method. Previous studies have shown similar results (Nedembale et al, 2004;Kuwayama , 2007;Rios et al, 2010;Trigal et al, 2012; attributed to the brief exposure to cryoprotectant, as described by Vajta et al (1998) and Mucci et al (2006). Membrane stability of in vitro produced bovine embryos might be an important factor determining their susceptibility and viability to freezing (Imai et al, 1997).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…We observed that bovine IVP embryos survived vitrification at higher rates than freezing by the slow-controlled rate method. Previous studies have shown similar results (Nedembale et al, 2004;Kuwayama , 2007;Rios et al, 2010;Trigal et al, 2012; attributed to the brief exposure to cryoprotectant, as described by Vajta et al (1998) and Mucci et al (2006). Membrane stability of in vitro produced bovine embryos might be an important factor determining their susceptibility and viability to freezing (Imai et al, 1997).…”
Section: Discussionsupporting
confidence: 70%
“…In terms of embryo survival after thawing/ warming, vitrification of IVP embryos has been proved to be at least as efficient (Inaba et al, 2011) or better (Vajta and Nagy, 2006;Trigal et al, 2012;Vajta, 2013) than slow-rate freezing, so it is not easy to decide for one methodology over the other; each laboratory should decide which one adapts better to their conditions (Caamaño et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Do mesmo modo, Trigal et al (2012) confirmaram o efeito individual do touro, assim como do tipo de sêmen sobre a taxa de blastocistos, que foi maior com o sêmen não sexado do que com o sexado.…”
Section: Resultsunclassified
“…Struktur gen SRY tersebut memiliki daerah sentral yang berkorelasi dengan HMG (homeobox) atau disebut dengan housekeeping gene (pada mamalia disebut dengan GADPH) yang memiliki daerah konservatif yang dapat membedakan antar spesies. Karakteristik SRY-HMG inilah yang biasa digunakan untuk penelitian DNA berbasis penentuan jenis kelamin (Taylor 2005 ;Choi et al 2009 ;Trigal et al 2012 ;Gokulakrishnan et al 2015).…”
Section: Pendahuluanunclassified